Allotment of carbon is responsible for disorders in proteins - Rajasekaran, Ekambaram (Biomedical Informatics, 2011)
Sequence stretches in proteins that do not fold into a form are referred as disordered regions. Databases like Disport describe disordered regions in proteins and web servers like PrDOS and DisEMBL, facilitate the prediction of disordered regions. These studies are often based on residue level features. Here, we describe proteins with disordered regions using carbon content and distributions. The distribution pattern for proteins with disordered regions is different from those that do not show disordered regions.